Production of Antibody (IgG) Against Aflatoxin B1 - Hassan, Fadia; Al- Jibouri, Muna; Mustafa, Khatab; Hashim, Abdul Kareem (Iraqi Journal of Science, 2023)
Aflatoxin B1 (AFB1) is a mycotoxin produced mainly by fungus Aspergillus flavus in food and feed . It is considered as a carcinogenic toxin for human and animals. The current study was designed for produce antibody (IgG) against aflatoxin B1.It was achieved by immunization of experimental animals (New Zealand White rabbits) with prepared antigen consist of aflatoxin B1-BSA Conjugate (100 and 200 μg ) concentrations, and detection of produced antibody using Ouchterlony double immunodiffusion and ELISA techniques,. Ochterlony and ELISA techniques revealed that, high titer of IgG antibody was obtained by rabbit’s immunize, and the titer of antibody was increased steadily during the immunization schedule. The highest titer of antibody reached up to 12800.